1982
DOI: 10.1002/anie.198207661
|View full text |Cite
|
Sign up to set email alerts
|

Photocyclization of 2‐Aryl‐1,1‐difluoroethylenes: Synthesis of Mono‐ and Difluorinated Polycyclic Arenes

Abstract: I I 1 B g LOO -30.0 200 10.0 10 20 30 LO 50 100 200 300 400 T pC]-P bfml-Fig. 2. Effective hydrodynamic radius, R,. of DODAC-vesicles at I atrn determined by dynamic light scattering. Temperature-induced phase transition. Broken line: phase transition. 0 -0 DODAC vesicle, xx dirnyristoylphosphatidylcholine vesicle; A -A DODAC-vesicle containing I l"/o (w/w) cholesterol. R,=k,, TK2/(3xqT); k H = Boltzmann constant, r = ( l / r , ) = D K ' with K =(4nn/A)sin(8/2), r,=time constant, D=diffusion coefficient: A) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This activating method was effective even for difluoroalkenes 1e − g bearing a methoxy or a hydroxy group, which were unsuitable under strong acid conditions (entries 5−7). The reaction of difluoroalkene 1j with a phenyl group tethered by an o -phenylene linkage afforded 9-fluorophenanthrene 5j in 54% yield, which confirms the generation of cyclic fluoroalkenes 5 as intermediates (Scheme ) 3 Cyclization of Difluoroalkene 1j 2 Cyclization of Difluoroalkenes 1 entryR 1 R 2 R 3 R 4 R 5 time (h) 2 (%) 1 a −(CH) 4 − H H H 2 89 ( 2a + 3a ) 2 H H H H H 2 89 ( 2b ) 3 H H H Me H 11 83 ( 2c ) 4 H Me H Me H 1 79 ( 2d ) 5 H OMe H Me H 47 70 ( 2e + 2f ) b 6 H H OMe Me H 0.5 66 ( 2f + 2k ) c 7 H OH H Me H 12 78 ( 2g + 2l ) d 8 H CF 3 H Me H 30 15 ( 2h ) 9 e H H H H n -C 5 H 11 22 65 ( 2i ) a The reaction was conducted at 0 °C.
…”
mentioning
confidence: 72%
“…This activating method was effective even for difluoroalkenes 1e − g bearing a methoxy or a hydroxy group, which were unsuitable under strong acid conditions (entries 5−7). The reaction of difluoroalkene 1j with a phenyl group tethered by an o -phenylene linkage afforded 9-fluorophenanthrene 5j in 54% yield, which confirms the generation of cyclic fluoroalkenes 5 as intermediates (Scheme ) 3 Cyclization of Difluoroalkene 1j 2 Cyclization of Difluoroalkenes 1 entryR 1 R 2 R 3 R 4 R 5 time (h) 2 (%) 1 a −(CH) 4 − H H H 2 89 ( 2a + 3a ) 2 H H H H H 2 89 ( 2b ) 3 H H H Me H 11 83 ( 2c ) 4 H Me H Me H 1 79 ( 2d ) 5 H OMe H Me H 47 70 ( 2e + 2f ) b 6 H H OMe Me H 0.5 66 ( 2f + 2k ) c 7 H OH H Me H 12 78 ( 2g + 2l ) d 8 H CF 3 H Me H 30 15 ( 2h ) 9 e H H H H n -C 5 H 11 22 65 ( 2i ) a The reaction was conducted at 0 °C.
…”
mentioning
confidence: 72%
“…Likewise, only difluorinated products were observed from oxidative cyclization of 2,5‐difluorophenylnaphthylethenes 18. In a related process, it has been demonstrated that monofluoro phenanthrenes can be prepared by irradiation of difluoroethylene precursors followed by an additional base mediated dehydrofluorination step 19…”
Section: Methodsmentioning
confidence: 99%
“…[18] In ar elated process, it has been demonstrated that monofluoro phenanthrenesc an be prepared by irradiation of difluoroethylenep recursors followed by an additional basem ediated dehydrofluorination step. [19] In the study we present here the elimination of hydrogen fluoridehas been found to be both general and efficient in the process of photocyclodehydrofluorination (PCDHF). In Scheme 1t his process for stilbenes has R 1 = F. The experimental methods we employ are designedt os uppress the oxidative route by exclusion of vicarious oxidants (such as oxygen) and abandon use of intentional oxidants (such as iodine).…”
mentioning
confidence: 98%
“…Reaction of 2.5 g (20 mmol) of 3-fluoro-1,2-xylene as described above for 4 afforded the bis(bromomethyl) compound 8 as a white solid, 3.0 g (53% yield). An analytical sample was recrystallized from ether/petroleum ether to give 8 as colorless plates: mp 41-42.5 °C; NMR 7.45-6.83 (m, 3), 4.78 (s, 2), 4.61 (s, 2); mass spectrum, m/e 1.2-Bis[(triphenylphosphonio)methyl]-3-fluorobenzene Dibromide (9). The bis(triphenylphosphonium) salt 9 was prepared from 8 (2.9 g, 10 mmol) as described above for 5.…”
Section: Methodsmentioning
confidence: 99%